1989
DOI: 10.1021/tx00012a006
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, analysis and anticholinesterase properties of O,O-dimethyl phosphorothioate isomerides

Abstract: Previous studies have shown that impurities in commercial organophosphorus insecticides induce a variety of toxicological manifestations. Few studies have contrasted common impurity types and their comparative chemical and biochemical properties. In this study, five O,O-dimethyl phosphorothioate compounds were converted to their corresponding O,S-dimethyl phosphorothioates (isomerides) by a stepwise dealkylation-alkylation process (yields 58-76%). The O,S-isomerides and parent material were characterized by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The sulfur originally present in diazinon was lost. The source of the diethoxyphosphate adduct at 3064.5 amu can be rationalized by invoking a thiono-thiolo rearrangement in which the double bonded sulfur on the phosphorus atom is exchanged with the oxygen on the pyrimidinol ring (Thompson et al, 1989; Barr et al, 2005). The rearranged isomer structure, S-pyrimidine O,O-diethylphosphate, is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfur originally present in diazinon was lost. The source of the diethoxyphosphate adduct at 3064.5 amu can be rationalized by invoking a thiono-thiolo rearrangement in which the double bonded sulfur on the phosphorus atom is exchanged with the oxygen on the pyrimidinol ring (Thompson et al, 1989; Barr et al, 2005). The rearranged isomer structure, S-pyrimidine O,O-diethylphosphate, is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The effi cient CE-catalyzed detoxifi cation reaction has been studied by using MAL as preferential substrate: the reaction competes with the CYP-catalyzed formation of MAL oxon (Thompson et al, 1989;Sultatos, 1994) which is not hydrolyzed by PON1. Kinetic characterization with a panel of HLMs showed that either CE-catalysed or CYP-catalysed reactions consist of two components, highly differing in their affi nity for the pesticide (Buratti et al, 2005;Buratti and Testai, 2005a).…”
Section: Opt Detoxifi Cationmentioning
confidence: 99%
“…Malathion toxicity, in a manner similar to all OPTs, depends on its bioactivation to the toxic metabolite malaoxon (Thompson et al, 1989;Sultatos, 1994), which inhibits acetylcholinesterase (AChE) (Forsyth and Chambers, 1989), causing the accumulation of acetylcholine within synapses and the consequent overstimulation of postsynaptic receptors. Impurities, such as isomalathion and various trimethylphosphorothioate esters, present in the technical grade malathion or formed during storage, can potentiate malathion-induced toxicity up to 10-fold (Pellegrini and Santi 1972;Aldridge et al, 1979) and have been considered responsible for other effects, including DNA lesions (Flessel et al, 1993;Blasiak et al, 1999).…”
mentioning
confidence: 99%